MEG analysis of neural dynamics in attention-deficit/hyperactivity disorder with fuzzy entropy. Issue 4 (April 2015) - Monge, Jesús; Gómez, Carlos; Poza, Jesús; Fernández, Alberto; Quintero, Javier; Hornero, Roberto
Highlights A novel description of ADHD neural dynamics is provided. We examine changes in MEG activity by means of fuzzy entropy and relative power. Frontal, posterior and left temporal regions showed significant differences. Our results suggest that ADHD brain abnormalities are widespread. Affecting areas may be the cerebellum, the striatum and the prefrontal cortex.